Endocrine-disrupting chemicals and the risk of gestational diabetes mellitus: a systematic review and meta-analysis - Dandan Yan; Yang Jiao; Honglin Yan; Tian Liu; Hong Yan; Jingping Yuan (BMC, 2022)
Abstract Objective To conduct a comprehensive systematic review and meta-analysis to estimate the relationship between endocrine-disrupting chemicals (EDCs), including polychlorinated biphenyls (PCBs), poly-brominated diphenyl ethers (PBDEs), phthalates (PAEs), and per- and polyfluoroalkyl substances (PFAS) exposure and risk of gestational diabetes mellitus (GDM). Methods Relevant studies from their inception to November 2021 were identified by searching EMBASE, PubMed, and Web of Science. The cohort and case-control studies that reported effect size with 95% confidence intervals (CIs) of EDC exposure and GDM were selected. The heterogeneity among the included studies was quantified by I 2 statistic. Publication bias was evaluated through the Begg and Egger tests. Results Twenty-five articles with a total of 23,796 participants were found. Results indicated that exposure to PCBs has a significant influence on the incidence of GDM (OR = 1.14; 95% CI = 1.00--1.31; n = 8). The risk of GDM was found to be associated with PBDE exposure (OR = 1.32; 95% CI = 1.15-1.53; n = 4). PAEs and PFASs exposure were also positively associated with the risk of GDM, with summary ORs of 1.10 (95% CI = 1.03-1.16; n = 7 for PAEs) and 1.09 (95% CI = 1.02-1.16; n = 11 for PFASs), respectively. When only cohort studies were considered, the summary OR between PCBs exposure and the risk of GDM was 0.99 (95% CI = 0.91-1.09; n = 5). Meanwhile, the summary ORs from cohort studies for PBDEs, PAEs, and PFASs exposure were 1.12 (95% CI = 1.00-1.26; n = 2), 1.08 (95% CI = 1.02-1.15; n = 5), and 1.06 (95% CI = 1.00-1.12; n = 8), respectively. The Beggs and Egger tests did not show publication bias, and the sensitivity analyses did not change the results in this meta-analysis. Conclusion These results support that exposure to certain EDCs, including PCBs, PBDEs, PAEs, and PFAS, increase the risk of GDM. Further large-sample epidemiologic researches and mechanistic studies are needed to verify the potential relationship and biological mechanisms. These results are of public health significance because the daily EDC exposure is expected to increase the risk of GDM development. Graphical Abstract